Potential of cadmium removal using activated carbon from sugarcane bagasse - Salim, Mohd. Razman (2015)
The production of activated carbon (AC) from sugarcane bagasse (SCB) was carried out using central composite design of response surface method to run a limited number of experiments with the possibility of revealing the interaction of three selected factors of temperature, time and nitrogen/steam flowrate at different levels. Two second order quadratic regression model equations were developed using statistical analysis with Design Expert software. The model was used for the prediction of removal of Cd2+ and carbon yield. Correlation coefficients (R2) were 0.957 for removal and 0.985 for yield, showing the sufficiency of the model in predicting response within 13 experimental runs. Characterization of the product with optimal performance which was produced at 900oC, with nitrogen/steam flow of 100 mL/min and activation time of 30 minutes, was carried out. Performance showed this AC sample was able to remove 62.42% Cd2+ from an aqueous solution with concentration 2 mg/L within 2 hours at optimized condition. Experimental results indicated that AC from SCB had good prospect for Cd2+ removal.